The effect of perceived usefulness and perceived security on QRIS continuance usage intention among Generation Z: Lifestyle as a moderating variable - Rayhan Anugerah Hadikusuma; Thamrin, Thamrin (Marketing Management Studies, 2025)
This study aims to determine the effect of Perceived Benefits and Perceived Security on the continuance Usage Intention of QRIS by Gen Z as a Cashless Society, with Lifestyle as a Moderating Variable. The methodology used is associative research, which seeks to identify the relationships between several independent variables and the dependent variable. The study population consists of Gen Z in Kota Padang, with a sample of 150 QRIS users selected through purposive sampling within a non-probability sampling method. Data were collected through a questionnaire using a Likert Scale and analyzed using SmartPLS software. The findings of this study indicate that (1) Perceived Benefits have a positive and significant effect on continuance Usage Intention, (2) Perceived Security has a positive but not significant effect on continuance Usage Intention, (3) Lifestyle does not moderate the effect of Perceived Benefits on continuance Usage Intention, and (4) Lifestyle weakens the relationship between Perceived Security and continuance Usage Intention.